2014
DOI: 10.3390/md12074214
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin Enhances the Level of Reduced Glutathione via the Nrf2-Mediated Pathway in Human Keratinocytes

Abstract: Fucoxanthin, a natural carotenoid, is abundant in seaweed with antioxidant properties. This study investigated the role of fucoxanthin in the induction of antioxidant enzymes involved in the synthesis of reduced glutathione (GSH), synthesized by glutamate-cysteine ligase catalytic subunit (GCLC) and glutathione synthetase (GSS), via Akt/nuclear factor-erythroid 2-related (Nrf2) pathway in human keratinocytes (HaCaT) and elucidated the underlying mechanism. Fucoxanthin treatment increased the mRNA and protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
3
38
0
1
Order By: Relevance
“…Moreover, PI3K inhibitors significantly abolished the neuroprotective effects of fucoxanthin. These results suggested that fucoxanthin produced neuroprotective effects at least partially via the activation of the prosurvival PI3K/Akt pathway, which is consistence with a report that fucoxanthin activated the PI3K/Akt cascade to decrease cell injury [ 31 ]. Moreover, fucoxanthin attenuated A β oligomer-induced increase of pERK in SH-SY5Y cells, indicating that the inhibition of proapoptotic ERK pathway participated in the neuroprotective effects of fucoxanthin.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, PI3K inhibitors significantly abolished the neuroprotective effects of fucoxanthin. These results suggested that fucoxanthin produced neuroprotective effects at least partially via the activation of the prosurvival PI3K/Akt pathway, which is consistence with a report that fucoxanthin activated the PI3K/Akt cascade to decrease cell injury [ 31 ]. Moreover, fucoxanthin attenuated A β oligomer-induced increase of pERK in SH-SY5Y cells, indicating that the inhibition of proapoptotic ERK pathway participated in the neuroprotective effects of fucoxanthin.…”
Section: Discussionsupporting
confidence: 88%
“…Biochemical experiments indicated that knockdown of NRF2 could increase MDA concentration and decrease concentration of SOD, GSH and CAT, enhancing the effects of laminarin in MRC-5 cells. Numerous studies have proved the protective role of NRF2 against oxidation in various cell types, keratinocytes ( Madduma Hewage et al, 2016 ; Zheng et al, 2014 ), pancreatic β-cells ( Dinić et al, 2016 ), mesenchymal stem cells ( Loseva et al, 2012 ), amongst others, elevating SOD, GSH and CAT cellular concentration. Besides, up-regulation of NRF2 was accompanied with suppressed MDA level during the amelioration of oxidative damage ( Xie et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the protective effects of fucoxanthin against oxidative damage were related to inhibition of apoptosis through down-regulation of Bax expression and increase of Bcl-2 expression [ 329 ]. More recently, Zheng et al [ 330 ] studied the antioxidant activity of fucoxanthin in HaCaT cells and showed that this treatment increased the expression of glutamate-cysteine ligase catalytic subunit (GCLC) and glutathione synthetase (GSS), two enzymes involved in reduced glutathione (GSH) synthesis. The mechanisms underlying these effects were related to activation of the transcription factor Nrf2 via PI3K/Akt, which in turn activated the transcription of ARE-driven GCLC and GSS genes, leading the synthesis of antioxidant GSH.…”
Section: Inflammation and Skin Cancermentioning
confidence: 99%